Crisis as opportunity: Implications of the nuclear conflict with Iran for the nuclear non-proliferation regime - Oliver Meier (Stiftung Wissenschaft und Politik (SWP), 2014)
The conflict over the Iranian nuclear programme represents the greatest challenge for international efforts to prevent nuclear proliferation. For decades Iran has been violating obligations contained in its safeguards agreement with the International Atomic Energy Agency (IAEA) in order to become nuclear weapons capable. But what impact does the conflict over Tehran's nuclear programme have on the nuclear non-proliferation regime? In three areas there is significant overlap between efforts to find a solution with Iran and broader discussions about strengthening non-proliferation norms, rules and procedures: verification of civilian nuclear programmes, limiting the ability to produce weapons-grade fissile materials, and nuclear fuel supply guarantees. The nuclear dispute with Tehran is likely to have specific effects in each of these fields on the non-proliferation regime's norms, rules and procedures. The ninth NPT review conference, which will take place from 27 April to 22 May 2015, offers an opportunity to draw lessons from the nuclear conflict and discuss ideas for further strengthening the regime. Germany is the only non-nuclear-weapon state within the E3+3 group and the strongest proponent of nuclear disarmament. As a supporter of effective multilateralism, Berlin also bears a special responsibility for ensuring that steps to strengthen nuclear verification and control efforts in the talks with Iran also reflect the non-nuclear-weapon states' interest in disarmament and transparency on the part of the nuclear-weapons states. (SWP Research Paper)
Keywords: 320